“PHILOSOPHY IN ACTION” IN THE TEXTS AND PRACTICES OF PETER WORLEY - FRUNZĂ, Mihaela (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
“Philosophy in Action” in the Texts and Practices of Peter Worley. If philosophy for children (P4C) aims to become a “reconstruction of philosophy” itself (Lipman, 1997:13), the PhiE (Philosophical Enquiry), an approach proposed by Peter Worley, represents a thorough reconstruction of the classical P4C. In my article, I intend to emphasize the differences between Peter Worley’s approach and the classical version offered by Matthew Lipman and his followers. My thesis is that Worley’s approach manages both to stimulate to a greater extent children abilities of critical thinking, and to constitute a genuine representation of “doing philosophy” from early ages. In other words, Peter Worley’s distinct version of P4C represents both literally and metaphorically “philosophy in action”.